ChemInform Abstract: Pd‐Catalyzed Alkynylation of 2‐Chloroacetates and 2‐Chloroacetamides with Potassium Alkynyltrifluoroborates. Issue 10 (11th March 2014) - Molander, Gary A.; Traister, Kaitlin M.
Abstract A protocol is developed to allow the coupling of N‐substituted chloroacetamides and analogous esters with alkynyltrifluoroborates to give β, γ‐alkynyl amides and esters in good yields.